Comparative Analysis of Cooling Systems in Solar Power Plants on System Performance - Imelda Martalata Siburian; Zuraidah Tharo; Rahmaniar Rahmaniar (INFOKUM, 2026)
Temperature increase in solar panels is one of the main factors that reduces energy conversion efficiency in Solar Power Plant systems. To address this issue, fluid-based cooling methods have become an effective alternative in maintaining panel performance stability. This study analyzes the performance comparison of cooling systems using freshwater and saltwater on panel temperature changes and their effects on power output efficiency. The experimental method was conducted by operating solar panels under the same solar radiation conditions, then applying two types of cooling fluids separately to observe differences in temperature reduction and electrical performance improvement. The analysis results show that both cooling methods can significantly reduce panel temperature, but there are differences in thermal characteristics between them. Cooling using saltwater demonstrates better heat transfer capability, but potentially causes corrosion effects in the long term. Meanwhile, freshwater provides quite effective cooling stability with lower damage risk. These findings provide a comprehensive overview regarding the selection of optimal cooling media to enhance PV system efficiency in tropical conditions.